The Nazi invasion, 1944 - Tarshis, Lauren; Dawson, Scott (New York : Scholastic Inc., 2014)
In 1944, Max and Zena Rosen escape from their Polish ghetto and the Nazis and join up with Jewish resistance fighters.
Christian Library, November 2014.
4.8
3-6
740L
Keywords: World War, 1939-1945 -- Jewish resistance -- Fiction; Holocaust, Jewish (1939-1945) -- Poland -- Fiction; World War, 1939-1945 -- Underground movements -- Fiction; Holocaust, 1939-1945 -- Poland -- Fiction; Nazis -- History -- Fiction; World War, 1939-1945 -- Jewish resistance -- Poland -- Fiction; Holocaust, Jewish (1939-1945) -- Fiction; Jews -- History -- Fiction; Nazis -- Fiction; Poland -- History -- 20th century -- Fiction; Action and adventure fiction; Historical fiction